The Digital Transformation of the Retail Electricity Market in Spain - Julián Chaparro-Peláez; Emiliano Acquila-Natale; Ángel Hernández-García; Santiago Iglesias-Pradas (Energies, 2020)
The deregulation of the electricity markets in the European Union and the transformation caused by digital technologies and customer-centric strategies have altered the industry ecosystem, forcing companies to adapt to the new scenario. This research study aims to give a global overview of the digital transformation and channel integration of free-market electricity retailers in Spain from a consumer’s perspective. The analysis includes all free-market electricity retailers that operate at the national scale, explores the level of digital transformation and channel integration of these companies based on a structured set of indicators, and measures them using the mystery shopper technique. The results show important differences between leading retailers and the rest of companies, evidence an important lag of the sector when compared to other retail markets and an overall lack of multichannel and omnichannel strategies, show a strong effort of retailers in online billing and self-service customer data management, and reveal shortcomings in the availability of communication channels with customers.